The Significance of Excursions in Teaching Science in School - Rakhmatullayeva Anor Khairullayevna (Zeta Repository, 2023)
Excursions are an important form of the educational process conducted by a teacher with a class or a certain group of students in accordance with the curriculum, in order to study the habitat of objects and their specific features in the natural environment or artificially created conditions outside it. school. It is known that biology as an academic subject acquaints students with nature, inorganic components of nature, changes in them and specific processes of life of living organisms, adaptation to the environment, ecological communities, features of metabolism and energy in them